Effect Of Hormone on Orthodontic Tooth Movement: A Review - Sadiq, Omar; Ghoul, Rand; Ghannam, Nidal; -Hussein Muhamad, Abu (Journal of Neonatal Surgery, 2025)
Hormones have an important influence on the rate of tooth movement, and information on their consumption is essential to adequately discuss treatment planning with patients. Orthodontic tooth movement results from the response of the periodontal tissue to orthodontic force, which leads to modeling and remodeling of the surrounding alveolar bone. The response is considered to occur through the activation of specific signaling pathways, many of which are known, all acting to ultimately result in tooth movement. The rate at which tooth movement occurs is dependent upon the ability of these pathways to effect metabolism of bone by the two main cell types responsible for tooth movement: osteoblasts and osteoclasts. GH can affect craniofacial growth and tooth formation and eruption. Therapeutic administration of eicosanoids resulted in increased tooth movement, whereas their blocking led to a decrease. Corticosteroid hormones, parathyroid hormone, and thyroxin have all been shown to increase tooth movement. Estrogens probably reduce tooth movement, although no direct evidence is available. Vitamin D3 stimulates tooth movement, and dietary calcium seemed to reduce it. Bisphosphonates had a strong inhibitory effect. This article covers each aspect of hormonal influence on orthodontics